Photoshop CS down & dirty tricks - Kelby, Scott (Voices that matter., 2003)
Bestselling author Scott Kelby (Editor of Photoshop User magazine) is back with an amazing new collection of Photoshop Down and Dirty Tricks, including how to create the same exact effects you see every day in magazines, on TV, at the movies, and on the Web. It's more of those eye-popping, jaw-dropping special effects that made Scott's previous version an award-winning worldwide smash hit! But this isn't just an update to his previous book--these are 100% ALL NEW EFFECTS from cover-to-cover to reflect the latest trends in Photoshop special effects and design. These are nothing but today's real world techniques--the same ones you see used by leading Photoshop photographers, designers, and special effect masters, and its all here in the only book of its kind. You'll learn the most closely guarded inside secrets for creating the latest cutting-edge effects, including techniques that have never been revealed before anywhere! And the book is written so clearly, and is so easy to follow, that you'll be able to create every one of these amazing effects yourself. You'll learn: Tricks professional photographers use to show off their work The most popular effects used by the big Hollywood studios The latest cutting-edge photographic special effects How to fake all kinds of studio shots (you'll be amazed how its done!) The type effects that are most in demand by clients How to get stunning 3D effects without using a 3D program How to turn simple snapshots into museum quality gallery prints The most asked for new Web effects Plus loads of advanced effects that look hard, but are easy, once you know the secrets But Down and Dirty tricks is more than just a just an effects book--it's a tips book too, because on every page Scott includes a cool tip, a quick trick, or a timesaving shortcut, making this an invaluable productivity tool too! Plus the whole book is packed with design techniques, creative ideas and stunning layouts that will help you unleash your own creativity. It's all here-- "Just the funk and not the junk" and if you're into Photoshop, you're absolutely gonna love it!